An Efficient Data Dissemination Protocol with Roadside Parked Vehicles' Assistance in Vehicular Networks. (7th November 2013) - Gong, Haigang; Liu, Nianbo; Yu, Lingfei; Song, Chao
Abstract : Data dissemination is a challenging problem in vehicular ad hoc networks (VANETs) due to the characteristics of VANETs such as highly dynamic topology, intermittent connectivity, and the road-constrained mobility. Observed from the fact that on-street parking is a common phenomenon in the city, the parked vehicles at roadside can also contribute their resources to the communications in network. In this paper, an efficient data dissemination protocol (EDP) for VANETS is proposed. Different from the existing works which consider mainly mobile vehicles or some expensive roadside infrastructure, EDP leverages the resources of parked vehicles at roadside to help in forwarding data. EDP groups the parked vehicles at roadside into a cluster, which buffers and relays data from mobile vehicles and manages the duplicates of data. Simulation results based on a real city map show that EDP achieves a higher delivery ratio and lower delivery delay.